2021
DOI: 10.3389/fphys.2021.712628
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in Aviation: Safety Risks, Preventive Strategies and Pharmacological Interventions

Abstract: Fatigue poses an important safety risk to civil and military aviation. In addition to decreasing performance in-flight (chronic) fatigue has negative long-term health effects. Possible causes of fatigue include sleep loss, extended time awake, circadian phase irregularities and work load. Despite regulations limiting flight time and enabling optimal rostering, fatigue cannot be prevented completely. Especially in military operations, where limits may be extended due to operational necessities, it is impossible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 146 publications
1
29
0
2
Order By: Relevance
“…Our findings are in line with the literature, although previous studies investigated the effects of caffeine and modafinil after longer periods of sustained wakefulness (Killgore et al, 2008; Wesensten et al, 2005; Wingelaar-Jagt et al, 2021). Modafinil sustains flight performance and mood state during continuous wakefulness when tested during simulated or in-flight operations, while the results for caffeine were mixed and inconclusive in these studies (Ehlert and Wilson, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are in line with the literature, although previous studies investigated the effects of caffeine and modafinil after longer periods of sustained wakefulness (Killgore et al, 2008; Wesensten et al, 2005; Wingelaar-Jagt et al, 2021). Modafinil sustains flight performance and mood state during continuous wakefulness when tested during simulated or in-flight operations, while the results for caffeine were mixed and inconclusive in these studies (Ehlert and Wilson, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, sleep-related factors were not considered in this study. Sleep deprivation and also an extended period of wakefulness may negatively affect performance (Wingelaar-Jagt et al, 2021). To best reflect circumstances of operational military aviation, the participants were not imposed with bedtimes or waking times; therefore, the time since the last sleeping period and the duration of that sleeping period differed between subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep loss is considered the primary cause of fatigue in aviators ( Caldwell et al, 2009 ; Gore et al, 2010 ; Caldwell et al, 2019 ; Morris et al, 2020 ; Wilson et al, 2020 ; Wingelaar-Jagt et al, 2021 ). However, multiple experimental, observational, and medical studies have identified biochemical mechanisms promoting the onset and maintenance of fatigue as well as sleepiness ( Raison et al, 2006 ; Raison et al, 2009 ; Dantzer et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%